2011
DOI: 10.1128/aac.01807-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Intracellular Killing Effects of Tigecycline against Clinical Nontyphoid Salmonella Isolates Using Ceftriaxone as a Comparator

Abstract: Salmonella is an important, worldwide food-borne pathogen. Resistance to fluoroquinolones and cephalosporins has been increasingly reported, and new therapeutic agents are desperately needed. In this study, we evaluated the in vitro antimicrobial susceptibility of clinical nontyphoidal Salmonella isolates to tigecycline. Antibacterial activity of tigecycline, ceftriaxone, and ciprofloxacin were investigated by time-kill studies and the murine peritonitis model. The MIC 50 /MIC 90 values of tigecycline, ceftria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Broad‐spectrum antimicrobial agents with activity against multi‐drug‐resistant NTS include tigecycline and carbapenems . Carbapenems have been shown to be active against Salmonella species in vitro , and meropenem has been reported to achieve high intracellular concentrations in human macrophages .…”
Section: Managementmentioning
confidence: 99%
“…Broad‐spectrum antimicrobial agents with activity against multi‐drug‐resistant NTS include tigecycline and carbapenems . Carbapenems have been shown to be active against Salmonella species in vitro , and meropenem has been reported to achieve high intracellular concentrations in human macrophages .…”
Section: Managementmentioning
confidence: 99%
“…Wild-type C57BL/6 mice (males or females) were given either tigecycline (6.25 mg/kg of body weight) (n ϭ 20) or saline (n ϭ 8) by subcutaneous injection twice a day for a total of 10 days. This dose of tigecycline was selected for the mice because it reaches the maximum concentration of drug in serum (C max ) of 1.17 g/ml, which is similar to a C max of 0.93 g/ml, which correlates to a dose of 100 mg every 12 hours in humans (16). The mice were approximately 5 weeks old at the beginning of the study.…”
Section: Animals and Housingmentioning
confidence: 99%
“…It was subsequently approved for the treatment of community-acquired pneumonia (11). Tigecycline is a broad-spectrum glycylcycline antibiotic that is potent against both Gram-positive and Gram-negative facultative and obligate anaerobes, including C. difficile (12)(13)(14)(15)(16). Tigecycline has a low MIC against C. difficile in vitro (17).…”
mentioning
confidence: 99%
“…This antibiotic has potent activities against a range of Gram‐positive and Gram‐ negative bacteria (Peterson, ). Tang et al () demonstrated bactericidal activities of tigecycline at 0.5 mgL −1 against intracellular S . Typhimurium in peripheral blood mononuclear cells.…”
Section: The Potency Of Existing Therapies Against Intracellular Pathmentioning
confidence: 99%